P2.144 Do Patients Have Confidence in Trained Non Medical Health Care Staff Screening For Sexually Transmitted Infections?. (13th July 2013) - Jackson, R M; Gill, M; Foley, E; Patel, R
Abstract : Background: In 2011, 1.3 million sexual health screens (SHS) were conducted in genitourinary medicine clinics across the UK, a doubling of workload in the last 8 years. One approach UK clinicians have adopted in managing this increase is for minimally trained non-medical staff (health care support workers (HCSWs)) to deliver protocol driven asymptomatic screening to low risk patients. There is limited research regarding patient confidence with the service offered by HCSWs and re-attendance rates could be an indicator of patient dissatisfaction. Aim: To assess whether patients who have asymptomatic screening with HCSWs were more likely to return for subsequent assessment by a clinician following discharge. Method: A case controlled study of 300 asymptomatic patients attending for sexual health screening between October 2011 and April 2012. There were 2 arms with equal patient numbers, the HCSW led clinic and the clinician led clinic. Data collection and analysis for both groups included patient demographics, diagnoses, treatment, test results and time to next new diagnosis. Results: No significant difference was found between the patient demographics of the two groups. The rates of Chlamydia infection between the HCSW and the clinician groups were 8% and 7.3% respectively. Within the clinician group 4 cases of syphilis, 1 new diagnosis of HIV and 1 case of Hepatitis C were also diagnosed. The HCSW clinic had 19 (12.7%) patients re-attend for further screening within 11 months compared to 16 (10.7%) patients who saw a clinician, showing no significant difference between the two groups [p = 0.124 Fishers exact test]. Only 1 patient from each group re-attended within 6 weeks for further screening due to the development of symptoms. Conclusion: This study highlights low patient re-attendance rates within the HCSW group. This is an indirect marker of patient satisfaction and demonstrates patients are reassured with the service they offer.